The family book about sexuality - Calderone, Mary (New York: Bantam Books, Inc., 1981)
Contents : Understanding ourselves as sexual persons,the human sexual response systems: how they develop and how they work,how human being have children: the human reproductive systems,family planning,living our sexual lives:influences and patterns during the life cycle,marriage,the family and its role in the development of sexuality
Includes bibliographical references and index
Keywords: Familia - Sexualidad